1993
DOI: 10.1017/s0022215100122406
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and complications of laryngectomy

Abstract: In an effort to establish factors responsible for our post laryngectomy fistulae we reviewed 357 patients who underwent total laryngectomy between 1965 and 1990, for laryngeal carcinoma. Pharyngocutaneous fistulae occurred in 84 cases (23 percent). There was no difference between the fistula group and the non-fistula group with regard to age, sex, general condition, or tumour differentiation. The only significant, positive association was with previous radical radiotherapy (10 fistulae out of 167 primary laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
70
1
6

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 13 publications
7
70
1
6
Order By: Relevance
“…Some retrospective studies have reported an increased incidence of wound and systemic complications for salvage laryngectomy after RT or CRT (9,10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies have reported an increased incidence of wound and systemic complications for salvage laryngectomy after RT or CRT (9,10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, primary closure of the pharynx may not be possible or may carry a high risk for pharyngocutaneous fistulas, [4][5][6][7][8] and primary reconstruction of these pharyngoesophageal defects is often required. The goals of reconstruction are to provide alimentary tract continuity and to restore speech and swallowing functions.…”
mentioning
confidence: 99%
“…Free vascularized tissue reinforcement of primary pharyngeal closure in salvage laryngectomy following failed organ preservation is effective in preventing major wound complications but did not reduce the overall fistula rate. Fistulas that developed following this technique were relatively small, did not result in exposed major vessels, and were effectively treated with outpatient wound care rather than readmission to the hospi- 5 for fistula development have been identified in various retrospective studies. With the advent of organ preservation therapy for advanced head and neck cancer, the use of combined chemotherapy and radiation therapy has become increasingly frequent.…”
mentioning
confidence: 99%